Second Five Year Plan 1956-61 Himachal Pradesh Government - Planning Commission (Planning Commission, 1956)
Technique of Gur Making be organised and all the growers of Sugar-cane at present manufacturing Gur may derive benefit from these demonstrations. the cost of the Capital Outlay on these Demonstration Parties will be about Rs. 30,000.
Himachal Pradesh Government, Industries Department